The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4212/cjhp.v66i4.1271
|View full text |Cite
|
Sign up to set email alerts
|

Online versus Live Delivery of Education to Pharmacists in a Large Multicentre Health Region: A Non-inferiority Assessment of Learning Outcomes

Abstract: Background:The prevalence of online modules for continuing education in the health professions has been increasing in recent years. However, the effectiveness of online modules for pharmacist learning has not been thoroughly studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…By the same token, equivalence or non-inferiority between the two methods could not be established due to the fact that there was no significant statistical difference in the educational outcome between CYPT and FLT in the superiority design [ 17 ]. To prove the hypothesis that student-led teaching was not inferior to faculty-led teaching, a non-inferiority study, which is now increasingly recognized as an effective methodological tool for professional healthcare education research [ 18 20 ], was required. In this study protocol, non-inferiority occurred when the lower limit of the 95% confidence interval (CI) for the difference in educational outcomes between the two teaching methods did not exceed the non-inferiority margin.…”
Section: Introductionmentioning
confidence: 99%
“…By the same token, equivalence or non-inferiority between the two methods could not be established due to the fact that there was no significant statistical difference in the educational outcome between CYPT and FLT in the superiority design [ 17 ]. To prove the hypothesis that student-led teaching was not inferior to faculty-led teaching, a non-inferiority study, which is now increasingly recognized as an effective methodological tool for professional healthcare education research [ 18 20 ], was required. In this study protocol, non-inferiority occurred when the lower limit of the 95% confidence interval (CI) for the difference in educational outcomes between the two teaching methods did not exceed the non-inferiority margin.…”
Section: Introductionmentioning
confidence: 99%
“…The interactive format was designed to facilitate engagement with the trainer, interest in content, and peer learning, collaboration (Herschell et al, 2010), and support (Taylor et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…They are increased knowledge and skills, access, information technology, transference of knowledge into practice, engagement, empowerment and confidence, and the need for support. The role of digital technology in rural health acknowledged how useful rural health professionals found online learning in terms of enhanced knowledge or skills or both (Abel et al, 2019;Bell and MacDougal, 2013;Berndt et al, 2017;Bond et al, 2018;Davies et al, 2013;DeSouza et al, 2020;Hills et al, 2010;Hunt-Smith and Butler, 2018;Lineker et al, 2019;Maguire et al, 2019;Regmi and Jones, 2020;Riley and Schmidt, 2016;Robinson et al, 2011;Sinclair et al, 2015;Sinclair et al, 2019;Taylor et al, 2013;Tchernegovski et al, 2014). Some studies found online learning to be as good as/or equivalent to face-to-face learning in relation to knowledge and satisfaction (for example, Berndt et al, 2017;Davies et al, 2013;Maguire et al, 2019;Taylor et al, 2013).…”
Section: Resultsmentioning
confidence: 99%